The Marquis of Montesclaros before and after being viceroy: Advantages and disadvantages of experience at the beginning of the 17th Century - Villarreal Brasca, Amorina (2024)
This paper analyses the career of the Marquis of Montesclaros in relation to the importance of experience as a fundamental requirement for carrying out the great offices of royal service and a principle of the political culture of the Spanish Monarchy. It presents the reasons given to justify his lack of experience at the beginning of his career, in the assistance of Seville, as well as his reflections after managing the two viceroyalties of the Indies and other important posts in the high administration. To this end, the article examines in depth a series of writings by the Marquis of Montesclaros that reveal the value placed on experience according to his stage of life and, especially, the flexibility that could be applied to the same principle according to the political times of the king’s court.